A conceptual framework on redefine transit-oriented development station to improve work-life balance among young urbanites - Mohd Zairul; Yoong, Sheng Wong; Md Noor, Md Pilus (Malaysia Architectural Journal, 2022)
In Malaysia, most are the user using public transport is working adult especially young urbanites. Young urbanites are fresh to employment and majority of them are renting room near to Transit-Oriented Development (TOD) station and riding public transport to work. Young Urbanites work over time until late 8 or 9 pm and they missed out the time for after work activities. This affected young urbanite work-life balance. However, the current TOD station only designed to connect with surrounding development. The Surrounding development may not provide the needs or facilities of young urbanites enjoy after their overtime working. Therefore, this study aim to redefine the concept and typology of TOD station to improve young urbanites work life balance. This study is to support a study on the future design of TOD station on providing additional function, facilities and amenities to improve quality of life of the TOD community and determine the needs and lifestyle among young urbanite and proposed series of facilities and amenities on TOD station to improve their work-life balance. This research will contribute a design guideline on TOD station in the future that can emerge with surrounding neighbourhood context and improve the engagement with the surrounding community. This research also help on designing TOD master planning in the future city. Therefore, this research giving a new reference or new model to TOD station with other function and activities to be a new node to the community surrounding.